“La Señora B” - González Sáez, Helena (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2007)
Ms.B’s art work at the art workshop, makes possible an interesting reflection around ideas of fragment, rest, collage and contemporaneity. The associations Ms. B formulates, and the forms these associations acquire, offer the opportunity to witness the transit of subjects placed among the real of the body - what can not be represented - toward the symbolic, toward the field of the ideal... Although this circuit seems impossible to be completed, Ms. B. describes the art workshop as what keeps her in touch with the Day Center.